The Stille reaction in natural product synthesis : the total synthesis of 14,15-anhydrovirginiamycin M2 - Jordan, Stuart Ian (1997)
The thesis describes synthetic studies directed towards the total synthesis of 14,15-anhydrovirginiamycin M2, a streptogramin antibiotic of the virginiamycin family. This novel natural product shows pronounced antibacterial activity against a wide range of potentially lethal bacteria. The Introduction summarises the main therapeutic uses, isolation, structural determination, biosynthesis, and mode of action of the virginiamycins. Also included is a review of synthetic approaches which have been described to access these and similar streptogramin antibiotics by other research groups. A review of the intramolecular Stille coupling reaction within organic synthesis incorporating the most prominent examples of its use over the past ten years in the synthesis of natural products is also presented. The Discussion part of the thesis contains details of our synthetic studies on suitable model systems, including: a study of conjugated triene formation via Stille chemistry; peptidic bond formation; and special reference to the problems involved in the synthesis of the 2,4-disubstituted oxazole contained within the virginiamycins. The studies culminate with a description of the first total synthesis of 14,15- anhydrovirginiamycin M2, which proved identical to the natural product obtained from a Streptomyces fermentation process. A full description of the experimental work carried out, and spectroscopic data for all compounds synthesised, is contained in an Experimental section.